THE PATHOLOGY OF THE SACROILIAC JOINT IS AN INTERDISCIPLINARY PROBLEM. NEUROLOGIST'S VIEW - Нина Константиновна Перевощикова; Инна Владимировна Давиденко (Медицина в Кузбассе, 2021)
Pain in the lower back is the most common complaint of patients in outpatient practice. Differential diagnosis is difficult, especially in the diagnosis of sacroiliac joint pathology (CPS). Difficulties in diagnosing sacroiliac joint dysfunction (pathology) explain the difficulties and errors in the treatment and prognosis of the disease.